Estimation of seroprevalence of melioidosis among adult high risk groups in Southeastern India by indirect Hemagglutination assay - Sruthi Raj; Sujatha Sistla; Deepthy Melepurakkal Sadanandan; Tamilarasu Kadhiravan; Palanivel Chinnakali (Public Library of Science (PLoS), 2022)
Burkholderia pseudomallei is an environmental saprophyte known to cause melioidosis, a disease endemic in northern Australia and Southeast Asia. With the increasing number of melioidosis cases, there is a lack of data on seroprevalence rates and extent of exposure in high risk population of melioidosis from different endemic regions in India. The present cross sectional study was undertaken to estimate the seroprevalence of melioidosis in high risk populations in and around Puducherry, a coastal town in Southeastern India. Blood samples were collected from 275 diabetic individuals attending a tertiary care centre in Southern India and 275 farmers residing under the rural field practice area of our hospital. The antibody levels were estimated using an Indirect Hemagglutination Assay. The overall seropositivity was found to be 19.8% with a titer ≥1:20. Farmers were 2.8 times more likely to be seropositive than non-farmers. Rates of seroprevalence among diabetic subjects were less compared to the non-diabetic individuals. The seropositivity rates in non-diabetic farmers were higher (56/203, 27.6%) compared to diabetic farmers (34/164, 20.7%). The lowest seropositivity was seen among diabetic non-farmers at 10.4%. Multivariable logistic regression analysis revealed domicile (adjusted odds ratio-aOR: 2.32, 95% Confidence interval-CI: 1.05, 5.13) and contact with animals (aOR: 1.89, 95% CI:1.04, 3.44) as significant predictors of seropositivity. None of the other socio-demographic factors including gender and age were significantly associated with seropositivity. This study demonstrates widespread exposure to B. pseudomallei among adults residing in and around Puducherry, including those engaged in non-farming occupations.